2017
DOI: 10.5348/ijbti-2017-32-oa-5
|View full text |Cite
|
Sign up to set email alerts
|

Iron overload in beta thalassemia major patients

Abstract: Aims: Beta thalassemia is the most common monogenic hereditary hemoglobin disorder, which poses a major health burden to SriLanka. Regular transfusions of erythrocytes required for survival of these patients lead to inevitable iron overload, which is manifested, by elevated serum ferritin levels. Progressive deposition of iron leads to dysfunction and failure of the major organs. The aim of this study was to evaluate the iron overload of the beta thalassemia major patients in one of the thalassemia centres in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 26 publications
0
10
3
1
Order By: Relevance
“…The mean serum ferritin level of our patient cohort was 1778 µg/l which is considerably lower than the value (2992 µg/l) reported in a recent study done among forty patients in another centre in Sri Lanka [ 16 ]. Similarly, two recent studies done in India [ 17 ] and Pakistan [ 18 ] reported very high mean serum ferritin values, 2767 and 4236 µg/l, respectively among patients with thalassaemia.…”
Section: Main Textcontrasting
confidence: 84%
“…The mean serum ferritin level of our patient cohort was 1778 µg/l which is considerably lower than the value (2992 µg/l) reported in a recent study done among forty patients in another centre in Sri Lanka [ 16 ]. Similarly, two recent studies done in India [ 17 ] and Pakistan [ 18 ] reported very high mean serum ferritin values, 2767 and 4236 µg/l, respectively among patients with thalassaemia.…”
Section: Main Textcontrasting
confidence: 84%
“…28 A positive association between duration of blood transfusion and degree of body iron was observed previously. 29 Furthermore, some studies reported positive correlations between serum ferritin and duration of transfusion and age of the patients. 29 Moreover, the interaction between CLNK and iron overload biomarkers may be explained by the formation of microvesicles in RBCs.…”
Section: Discussionmentioning
confidence: 99%
“…29 Furthermore, some studies reported positive correlations between serum ferritin and duration of transfusion and age of the patients. 29 Moreover, the interaction between CLNK and iron overload biomarkers may be explained by the formation of microvesicles in RBCs. Bailey et al (2007) 7 found that the cyclic adenosine monophosphate (cAMP)-dependent pathway plays a role in γ-globin gene (HBG) expression in adult erythroblasts in β-thalassaemia.…”
Section: Discussionmentioning
confidence: 99%
“…The pretransfusion hemoglobin level was done on cell Dyne-3700 fully automated cell counter (Abbott Diagnostics, Wiesbaden, Germany). The pretransfusion levels over one year period were traced from the past medical records of the patients and the average was considered as the mean pretransfusion hemoglobin level [29]. The diagnosis of β-thal was confirmed by high-performance liquid exchange chromatography (HPLC) using Hemoglobin A1c/A2/F BIO-RAD D-10 dual program on D-10 analyzer (Bio-Rad, Gladesville, Australia).…”
Section: Hematological Assessmentmentioning
confidence: 99%